2021
DOI: 10.1038/s41598-021-91847-3
|View full text |Cite
|
Sign up to set email alerts
|

Varied-shaped gold nanoparticles with nanogram killing efficiency as potential antimicrobial surface coatings for the medical devices

Abstract: Medical device-associated infections are a serious medical threat, particularly for patients with impaired mobility and/or advanced age. Despite a variety of antimicrobial coatings for medical devices being explored to date, only a limited number have been introduced for clinical use. Research into new bactericidal agents with the ability to eradicate pathogens, limit biofilm formation, and exhibit satisfactory biocompatibility, is therefore necessary and urgent. In this study, a series of varied-morphology go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 67 publications
3
49
3
Order By: Relevance
“…The motivation for selecting rod-shaped nanoparticles to the induction of the development of resistance of Candida strains was dictated by the previous research. The results obtained by Piktel et al showed no substantial differences between rod-, peanut-, and star-shaped gold nanoparticles [39]. Comparable conclusions were also drawn in our other research, where the negligible distinction on viability of Staphylococcus aureus Xen30, S. epidermidis 175, Klebsiella pneumoniae 700603, K. oxytoca 329, Pseudomonas aeruginosa LESB58, and P. aeruginosa 510 among rod-, peanut-, and star-shaped gold nanosystems was observed.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The motivation for selecting rod-shaped nanoparticles to the induction of the development of resistance of Candida strains was dictated by the previous research. The results obtained by Piktel et al showed no substantial differences between rod-, peanut-, and star-shaped gold nanoparticles [39]. Comparable conclusions were also drawn in our other research, where the negligible distinction on viability of Staphylococcus aureus Xen30, S. epidermidis 175, Klebsiella pneumoniae 700603, K. oxytoca 329, Pseudomonas aeruginosa LESB58, and P. aeruginosa 510 among rod-, peanut-, and star-shaped gold nanosystems was observed.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, Jebali et al confirmed that the antifungal properties of silver and gold nanocubes against Candida isolates were greater than gold and silver nanospheres and wires [41]. The above assumption was further supported by other results where a potent bactericidal activity of non-spherical nanosystems in comparison to spherical-nanoparticles was observed [39].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…and, in particular, C. albicans are prone to develop biofilms on indwelling devices [25] that offer this fungus new niches to colonize, and to use as an entry route to deeper sites. To reduce the infection burden due to biofilmcolonized medical devices, the use of compounds with anti-adhesive properties to coat or to functionalize biomaterials is also under investigation [26,27]. Among genitourinary infections, Candida is also a common etiological agent of vulvovaginitis [28], affecting a high percentage of women at reproductive age.…”
Section: Discussionmentioning
confidence: 99%
“…By fine tuning the components and concentrations, AuNPs can be easily manufactured into various forms and sizes [28][29][30]. AuNPs have also shown significant advancement in treating inflammatory diseases and bacterial infections [31,32].…”
Section: Introductionmentioning
confidence: 99%